The Time Course of Monocytes Infiltration After Acoustic Overstimulation - Shin, Seung Ho; Jung, Jinsei; Park, Haeng Ran; Sim, Nam Suk; Choi, Jae Young; Bae, Seong Hoon (Frontiers in Cellular Neuroscience, 2022)
Cochlea macrophages regulate cochlea inflammation and may harbors the potentials to protect hearing function from injury, including acoustic overstimulation. Cochlea macrophage numbers increase at 3–7 days after acoustic stimulation. However, the exact timing of macrophage infiltration and maturation from inflammatory monocytes is unclear. Furthermore, neutrophils may also be involved in this process. Therefore, in this study, we investigated time-dependent immune cell infiltration, macrophage transformation, and neutrophil involvement following acoustic stimulation. Flow cytometry and immunofluorescence were conducted in C-X3-C motif chemokine receptor 1 (CX3CR1)+/GFP mice after acoustic overstimulation (at baseline and at 1, 2, 3, and 5 days after exposure to 120 dB for 1 h) to identify inflammatory monocytes in the cochlea. RNA-sequencing and quantitative polymerase chain reaction were performed to identify differentially expressed genes. Inflammatory monocytes infiltrated into the lower portion of the lateral wall within 2 days after acoustic overstimulation (dpn), followed by transformation into macrophages at 3–5 dpn via CX3CR1 upregulation and Ly6C downregulation. In addition, inflammatory monocytes were aggregated inside the collecting venule only at 1 dpn. Neutrophils were not observed at any time point. The gene encoding C-C motif chemokine ligand 2 gene was significantly upregulated as early as 3 h after acoustic overstimulation. Given these results, treatment to control immune response after a noise-induced hearing loss should be applied as soon as possible.